An Analysis of the Role of Software Engineering in Improving the Quality of Academic Information Systems at Wirahusada University Medan - Dybio Dompu Hot Asih; Dede Ardian Tarigan; Jona Efranata Tarigan (Eastasouth Institute, 2026)
Software engineering plays a crucial role in ensuring the quality of information systems used in higher education institutions. This study aims to analyze the role of software engineering practices in improving the quality of academic information systems at Wirahusada University Medan. The research focuses on how systematic software engineering processes contribute to system reliability, usability, and maintainability. This study employs a descriptive research method with a case study approach. Data were collected through observations, interviews, and questionnaires involving system users and developers. The analysis results indicate that the application of software engineering principles, including requirements analysis, system design, implementation, and testing, has a significant impact on improving system quality. The findings show that structured development processes enhance system performance, reduce errors, and increase user satisfaction. Therefore, the implementation of proper software engineering practices is essential to ensure the quality and sustainability of academic information systems in higher education institutions.